DETERMINAN KETIMPANGAN PENDAPATAN DI PULAU JAWA - Fathurrahman, Ayif (Universitas Negeri Gorontalo, 2026)
Income inequality is a development problem that cannot be eliminated in developed or developing countries. The difference lies in the degree of inequality and how to overcome the problem. Java Island has a high level of inequality when compared with other islands in Indonesia. This research aims to analyze the factors that influence income inequality on the island of Java 2013-2021. The data used in this research is secondary data in the form oftime series 2013-2021 andcross section 6 provinces obtained from the Central Statistics Agency. The data analysis method used in this research is panel data regression analysis with a modelfixed effect on the program Eviews 10. The results of this study show that the GDP per capita variable has a positive and significant effect on income inequality, TPT has a positive and significant effect on income inequality, HDI has a negative and significant effect on income inequality, the poverty level has a negative and insignificant effect on income inequality.